TikTok as a Marketing Medium: The Influence of User Generated Content (UGC) and Viral Marketing on Online Purchase Decisions on Glad2Glow Skincare Products - Hikmah Akbar Robiul Ramadhan; Tri Yeni; Misbak Misbak; Tiara Muthiarsih (Rescollacom (Research Collaborations Community), 2025)
TikTok social media has evolved into a social commerce platform, serving as an effective digital marketing tool. This study aims to ascertain how user-generated content (UGC) and viral marketing influence online purchasing decisions, with a case study on Glad2Glow products. Using quantitative methods and SPSS (Statistical Product and Service Solutions) version 22, this study utilized Roscoe's formula and used a purposive sampling approach with 210 respondents who met the criteria of TikTok users who had purchased Glad2Glow products. The findings of this study indicate that user generated content (UGC) and viral marketing influence the decision to buy Glad2Glow products online. With a determination value of R square of 0.764 or 76.4%, the research findings show that viral marketing is the most important component in spreading the message widely. User Generated Content (UGC), with a determination value R square User Generated Content (UGC) of 0.534 or 53.4%, states that User Generated Content (UGC) has an important role in building understanding before purchasing a product. These findings provide deeper insights into the effectiveness of digital marketing strategies through TikTok, as well as how the combination of User Generated Content and viral marketing can influence online purchasing decisions.